Procedural and legal status of the injured party according to the new criminal procedure code of the Republic of Serbia - Grubač Momčilo (Temida)
In this article the author is critically analyzing certain solutions of the new Criminal Procedure Code of the Republic of Serbia from 2011 which consider the injured party and their rights in the criminal proceeding. He states that unlike the previous ones, this Code does not improve the status of the injured party but makes it even worse. The author particularly claims that the legislator yet again failed to establish the right of the injured party to be efficiently compensated in the event of a serious offense from a special fund and immediately after the crime has been committed, but prior to the end of the criminal proceeding. In the provision of the Code which states that the injured party may take over the prosecution and become a prosecutor replacing the Public Prosecutor (subsidiary prosecutor) only if the Public Prosecutor withdraws after having confirmed the indictment, however not in the cases of rejection of criminal charges or withdrawal from the prosecution in the previous proceeding, the author sees not only the limitation of the rights of the injured party, but also jeopardy of the public interest. This is due to the fact that, freed from a threat of the subsidiary accusation by the injured party, the Public Prosecutor has gained an absolute and uncontrolled monopoly over the initiation of criminal proceeding. According to the author, the subject of the proceedings will not have any substantial use from some rights which the new Code assigns to the injured party (for example the right to appeal against the judgment on the adjudicated property claim). In conclusion, the author stresses out that in spite of his objections against certain provisions in the Code, the legal status of the injured party is more favorable in the criminal law of Serbia then in many other countries.